Differential responses of arbuscular mycorrhizal fungal communities to mineral and organic fertilization. Issue 1 (8th August 2019) - Liu, Jia; Zhang, Jie; Li, Daming; Xu, Changxu; Xiang, Xingjia
Abstract: Agricultural fertilization is used extensively to increase soil fertility and maximize crop yield. Despite numerous studies on how fertilization influences plant and bacterial communities, little is known about the roles of long‐term application of different fertilizers in shaping arbuscular mycorrhizal fungal (AMF) community structures in a comparative manner. The response of AMF community to 28 years of chemical and organic fertilization was investigated using the Illumina Mi‐Seq platform. Soil AMF community composition showed significant and differential responses to long‐term fertilization. Changes in available phosphorus (AP) content were the primary driver shaping AMF community composition. Chemical fertilization significantly decreased AMF alpha‐diversity, whereas the alpha‐diversity remained equally high in organic fertilization treatment as in the control. In addition, soil AMF alpha‐diversity was negatively and positively correlated with elevated soil nutrient level following chemical and organic fertilization, respectively. Plants could directly acquire sufficient nutrients without their AMF partners after chemical fertilization, while plants might rely on AMF to facilitate the transformation of organic matter following organic fertilization, indicating that chemical fertilization might reduce the reliance of plants on AMF symbioses while organic fertilization strengthened the symbiotic relationship between plants and their AMF partners in agricultural ecosystems. This study demonstrated that AMF communities responded differently to long‐term chemical and organic fertilization, indicating that organic fertilization might activate belowground AMF function to maintain soil nutrients and benefit the sustainable development of agriculture. Abstract : Soil AMF community composition showed significant response to long‐term fertilization whose effects were different following chemical and organic fertilizer treatments. Besides, soil AMF community composition was shaped by soil nutrient contents which were asymmetrically changed following chemical and organic fertilization, suggesting that the different responses of AMF community composition were mediated by fertilization‐type‐induced shifts in soil nutrient contents. Chemical fertilization significantly decreased AMF alpha‐diversity which showed similar level following organic fertilization relative to control samples. In addition, soil AMF alpha‐diversity showed negative and positive correlation with elevated soil nutrient level following chemical and organic fertilization, respectively. Plant could directly acquire sufficient nutrients without their AMF partner after chemical fertilization, while plant might rely on AMF to facilitate the transformation process of organic matters following organic fertilization, indicating that chemical fertilization might reduce reliance of plants on AMF symbioses while organic fertilization strengthened the symbiotic relationship between plant and AMF partner in agricultural ecosystem.